Different patterns of changes in free 25-hydroxyvitamin D concentrations during intermittent fasting among meat eaters and non-meat eaters and correlations with amino acid intake. (17th February 2023) - Karras, Spyridon N.; Koufakis, Theocharis; Adamidou, Lilian; Dimakopoulos, Georgios; Karalazou, Paraskevi; Thisiadou, Katerina; Zebekakis, Pantelis; Makedou, Kali; Kotsa, Kalliopi
Abstract: We prospectively assessed changes in free 25-hydroxyvitamin D [25(OH)D] and vitamin D binding protein (VDBP) among overweight adults who followed a pescatarian Orthodox intermittent fasting regimen ( n = 59) and controls who followed a low-fat 12:12 diet ( n = 46). Total and free 25(OH)D, parathyroid hormone, VDBP, anthropometric data, and amino acid intake were evaluated in both groups at three time points: at baseline, 7 weeks after diet implementation, and 5 weeks after participants returned to their usual eating habits (12 weeks from baseline). An increase in amino acid intake between baseline and 12 weeks was independently correlated with higher free 25(OH)D values at 12 weeks for both groups. Our findings suggest that diet can affect free 25(OH)D concentrations, through variations in amino acid intake, independently of exposure to sunlight, providing novel mechanistic insights into the future planning of vitamin D supplementation strategies. However, this hypothesis needs to be tested in larger studies.